'I have been all in, I have been all out and I have been everything in‐between': A 2‐year longitudinal qualitative study of weight loss maintenance. Issue 1 (21st October 2020) - Thom, G.; Lean, M. E. J.; Brosnahan, N.; Algindan, Y. Y.; Malkova, D.; Dombrowski, S. U.
Abstract: Background: Qualitative studies investigating weight management experiences are usually cross‐sectional or of short duration, which limits understanding of the long‐term challenges. Methods: Eleven women [mean (SD) age 44.9 (9.8) years; body mass index 40.3 (4.0) kg m −2 ] participated in this longitudinal qualitative study, which included up to 20 weeks of total diet replacement (825–853 kcal day −1 ) and ongoing support for weight loss maintenance (WLM), to 2 years. Semi‐structured interviews were conducted at baseline and programme end, as well as at key intervals during the intervention. Questions examined five theoretical themes: motivation, self‐regulation, habits, psychological resources and social/environmental influences. Data were coded and analysed in nvivo (https://qsrinternational.com/nvivo ) using the framework method. Results: In total, 64 interviews were completed (median, n = 6 per participant). Mean (SD) weight loss was 15.7 (9.6) kg (14.6% body weight) at 6 months and 9.6 (9.9) kg (8.8% body weight) at 2 years. The prespecified theoretical model offered a useful framework to capture the variability of experiences. Negative aspects of obesity were strong motivations for weight loss and maintenance. Perceiving new routines as sustainable and developing a 'maintenance mindset' was characteristic of 'Maintainers', whereas meeting emotional needs at the expense of WLM goals during periods of stress and negative mood states was reported more often by 'Regainers'. Optimistic beliefs about maintaining weight losses appeared to interfere with barrier identification and coping planning for most participants. Conclusions: People tended to be very optimistic about WLM without acknowledging barriers and this may undermine longer‐term outcomes. The potential for regain remained over time, mainly as a result of emotion‐triggered eating to alleviate stress and negative feelings. More active self‐regulation during these circumstances may improve WLM, and these situations represent important targets for intervention. Abstract : The present study comprised a longitudinal, theory‐based qualitative study, including up to 20 weeks of total diet replacement (825–853 kcal day −1 ), which aimed to examine the dynamic changes in perceptions of weight loss, weight loss maintenance and weight regain in individuals participating in a 2‐year weight management programme. In total, 64 interviews were completed (median, n = 6 per participant) and mean (SD) weight loss was 15.7 (9.6) kg (14.6% body weight) at 6 months and 9.6 (9.9) kg (8.8% body weight) at 2 years. There was no single defining feature or experience common to all participants. People tended to be very optimistic about WLM without acknowledging barriers and this may undermine outcomes. The potential for regain remained over time, mainly as a result of emotion‐induced eating to alleviate stress and negative feelings. More active self‐regulation during these circumstances may improve outcomes, and these situations represent important targets for intervention.